Acne Keloidalis Nuchae: A Multicenter Retrospective Study of 142 Hispanic Patients - Luis E. Sánchez-Dueñas; Mariana G. Ungson-García; Joel Alejandro Ramirez Sanchez; Ayala Barrera Antonio Michell; Marti Machado Miguel; Sonia Sofía Ocampo-Garza; Lizet K. Rojano-Fritz; Aldo Gálvez-Canseco; Lidia Elena Bernal López; Daniela Gutierrez Mendoza; Roxana Castañeda Yepiz; Araceli Alvarado Delgadillo; et al. (Dermatology Practical & Conceptual, 2024)
Introduction: Acne keloidalis nuchae (AKN) is a primary cicatricial alopecia with mixed infiltrate. It is more common in African or persons of African descent.